The Role of Transforming Growth Factor-Beta, Fibroblast Growth Factor, Platelet-derived Growth Factor, Epidermal Growth Factor, Insulin-like Growth Factor, Vascular Endothelial Growth Factor, and Sonic Hedgehog in the Non-syndromic cleft lip with or without cleft palate development: A Scoping Review - Ullah, Irfan; Khan, Muhammad Salman; Nasroen, Saskia Lenggogeni; Maskoen, Ani Melani; Sarilita, Erli (Departemen Kimia, 2024)
Non-syndromic cleft lip with or without cleft palate (NSCLP) birth defect, it imposes an enormous stress on society and requires nutrition, dental, speech, behavioural, and surgical therapies. The NSCLP multifactorial aetiology, including the environment and genetic factors. The environment and genetic factors affect the cellular mechanism, cell proliferation, cell differentiation, and cell migration and signalling pathways. Genetic growth factors including Transforming Growth Factor-Beta (TGF-β), Fibroblast Growth factors (FGFs), Platelet-derived Growth factors (PDGFs), Epidermal Growth factor (EGF), Insulin-like growth factors (IGF), Vascular Endothelial Growth factor (VEGF), Sonic Hedgehog (SHH). The study aims to understand the role of the growth factors “TGF-β, FGFs, PDGFs, EGF, IGF, VEGF, and SHH” in NSCLP development. Preferential Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) standards were followed when performing this scoping review. The 942 articles were extracted, and the following inclusion and exclusive criteria 43 articles were eligible for review. Twenty-seven studies identify 26 genes and 25 single-nucleotide polymorphisms (SNPs)/variants of the growth factors that are a significant risk for NSCLP development. In conclusion, the analysis of diverse populations and growth factors including TGF-β, FGFs, PDGFs, EGF, IGF, VEGF, and SHH were associated with NSCLP. The growth factors were involved in the cellular mechanism, cell proliferation, cell differentiation cell migration and signalling pathways that lead to the pathogenesis of NSCLP.